2018
DOI: 10.18502/ken.v3i2.1822
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Electron Spectral Changes of Irradiated Gold Nanoparticle Caused By PEGylation

Abstract: Gold nanoparticles attract attention for the use in radiation therapy of tumors due to the ability to enhance the efficacy of ionizing radiation. The magnitude of the radiosensitizing effect depends on the parameters of the nanoparticle, in particular on the modification of the surface. In the present work, the spectrum of secondary particles generated in a gold nanoparticle virtually irradiated with 60 Со gamma rays as a result of surface modification by a polyethylene glycol shell was studied. The MonteCarlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Within the uncertainties of the present experiment, it may also be reasonably applicable at lower electron energies, although caution should be taken when considering different coating thicknesses or materials (or even a coating plus conjugated biomolecules). A study by Morozov et al [56] showed a 51% suppression of low-energy electrons in the energy range below 3 keV for a PEG coating thickness of 8.5 nm. This thickness is comparatively large compared to the values reported in the review by Kuncic and Lacombe [6].…”
Section: Use Of the Results For Benchmarkingmentioning
confidence: 98%
“…Within the uncertainties of the present experiment, it may also be reasonably applicable at lower electron energies, although caution should be taken when considering different coating thicknesses or materials (or even a coating plus conjugated biomolecules). A study by Morozov et al [56] showed a 51% suppression of low-energy electrons in the energy range below 3 keV for a PEG coating thickness of 8.5 nm. This thickness is comparatively large compared to the values reported in the review by Kuncic and Lacombe [6].…”
Section: Use Of the Results For Benchmarkingmentioning
confidence: 98%